(untitled) (Journal of Medical & Health Sciences Review, 2025)
BACKGROUND: Needle stick injuries (NSIs) are common occupational hazards among healthcare workers, particularly student nurses, posing a risk of exposure to blood-borne pathogens such as Hepatitis B, Hepatitis C, and HIV. OBJECTIVE: This study aimed to assess the prevalence, knowledge, and practices related to NSIs among student nurses during clinical training. METHODS: A descriptive cross-sectional study was conducted among 88 undergraduate student nurses at Liaquat College of Nursing, Jamshoro. Participants were recruited using convenience sampling. Data were collected through a structured, self-administered questionnaire covering demographics, NSI experience, knowledge, and safety practices. Data were analyzed using SPSS version 26. Descriptive statistics were calculated, and associations between demographic variables and NSI knowledge were examined using the Chi-square test, with significance set at p ≤ 0.05. RESULTS: Among participants, 47.7% reported experiencing NSIs, mostly during medication administration (43.2%) and cannulation (44.3%). Patient movement (39.8%) and needle recapping (34.1%) were the main causes. Most students had high knowledge of NSI definitions and immediate post-exposure actions (90.9%), but knowledge was lower regarding sharps disposal (21.6%), blood-borne pathogens (35.2%), and sharps container capacity (39.8%). Although 59.1% reported injuries occurring, only 45.5% cleaned the site with antiseptics, and 29.5% received post-exposure prophylaxis. Higher knowledge was significantly associated with year of study (p = 0.028), clinical training on needle/sharp handling (p = 0.012), and Hepatitis B vaccination status (p = 0.042).